IN VITRO-IN VIVO CORRELATIONSHIP APPROACH OF THE PREPARED MAGNETIC MICROSPHERES OF CYTARABINE - SATINDER KAKAR,; ANUREKHA JAIN, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to study the in vitro-in vivo correlationship between the magnetic microspheres prepared by continuous solvent evaporation (CSE) method by 32 factorial designs. Methods: CSE technique was used in the preparation of magnetic microspheres. Drug used was cytarabine and mice were the animal model used to check the correlationship. Results: The profiles are nearly identical and reveal that drug absorption is rapid. The in vivo drug absorbed was found to be in concordance with the in vitro release as seen in the superimposable curves. Conclusion: Cytarabine effectively reduces the amount of drug released and consequently absorbed in vivo in the initial phase.